(3MjGI GdEeGe Ydj (B/s - (3TdHj, eMehOs ((3dHfGf (B:s (3OGQ GdLjd ,s)
(3ajg(B...(3eG ajg heG GOQGc(B..... (3eG ajg(B..... (3ajg(B.... (3MjGI Ydj heG GOQGc eG MjGI Ydj(B...(3HMQ RNGQ(B...(3eG dg ef bQGQ(B...(3GdGeGe(B... (3GejQ GdeDefjf(B... (3GdUOjb GdGcHQ(B....(3QLd jMH Gddg h QShdg (B.... (3h jMHg Gddg h QShdg QLd eG SHbg GdGhdhf h dG jOQcg GdGNQhf (B...(3QLd bGd dg QShd Gddg(B....(3Udi Gddg Ydjg h Sde(B...(3GfJ efj (B.... (3HefRdI gGQhf ef ehSi(B.... (3GdG Gfg djS ef HYOj fHj Ydj GdSdGes
Keywords: (3GdEeGe Ydjs; (3bUIs